Efficacy of Particulate versus Non-Particulate Corticosteroids as Adjuvants for Popliteal Sciatic Nerve Block: A Randomized Controlled Superiority Trial - Erma Rosita; Taufiq Agus Siswagama; Rudy Vitraludyono; Buyung Hartiyo Laksono (Journal of Anesthesiology and Clinical Research, 2026)
Introduction: Single-shot ultrasound-guided popliteal sciatic nerve blocks are the gold standard for distal lower limb analgesia but are limited by a finite duration, often necessitating adjuvants. While dexamethasone (non-particulate) is the standard of care, methylprednisolone (particulate) theoretically offers a depot effect for sustained release. This study aimed to determine if perineural methylprednisolone provides superior analgesic duration compared to dexamethasone. Methods: In this prospective, double-blind, randomized controlled trial, 36 ASA I-III patients undergoing distal lower limb surgery were randomized (1:1) to receive 20 mL of 0.5% Ropivacaine with either Dexamethasone 8 mg (Group D) or Methylprednisolone 40 mg (Group M). To ensure blinding, solutions were prepared by an independent pharmacist and administered via opaque syringes. The primary outcome was the duration of analgesia (time to Numeric Rating Scale [NRS] greater than 3), analyzed using Kaplan-Meier survival curves and Log-Rank tests. Secondary outcomes included cumulative opioid consumption, rebound pain severity, and block onset time. The study was powered for superiority with a clinically significant difference of 4 hours. Results: Thirty-six patients completed the study. Demographic and surgical characteristics were comparable. The median duration of analgesia was 18.4 (SD 3.2) hours in Group D and 19.1 (SD 3.5) hours in Group M (p = 0.58; Log-Rank p = 0.61). Pain scores at 12, 24, and 48 hours showed no significant difference, with both groups demonstrating a floor effect due to multimodal analgesia (Median NRS less than 2). No adverse events, including neurotoxicity or infection, were observed. Conclusion: Perineural methylprednisolone failed to demonstrate superior analgesic duration compared to dexamethasone in this cohort. The theoretical depot advantage did not translate to clinical superiority, likely due to vascular clearance in the popliteal fossa. Given the comparable efficacy but superior safety profile of non-particulate agents, dexamethasone remains the preferred adjuvant. Methylprednisolone serves as a viable alternative only when non-particulate options are unavailable.